Analysis and Design of Enterprise Architecture PT Unilon Textile Industries on Human Resource Function (HR) And Procurement Using Togaf ADM - Fadhilah, Budiwari Rizki; Andreswari, Rachmadita; Hanafi, Ridha (Jurnal Rekayasa Sistem & Industri, 2018)
PT Unilon Textile Industries is one of the leading textile companies located in Bandung. The company is very concerned in current textile modes so it always prioritize the product which they are produce. To be able to produce quality products, it will require the function of human resources and good procurement function. In support of the implementation of these functions, technology that aligned with business process of the company needed. In aligning the business process and technology in a company, it is necessary to design an enterprise architecture on the function of human resources and procurement function. The design of enterprise architecture is done using TOGAF ADM because it has a systematic method. In this research, the design of enterprise architecture is done in preliminary phase, architecture vision, business architecture, information system architerture, technology architecture, opportunities and solution, and migration planning. Research is done by comparing the existing state of the company and the proposed target situation. The result of this research is blueprint to make IT Roadmap PT Unilon Textile Industries.